Impact of Socialization and Technical Guidance Program on Implementation of Independent Curriculum Independently - Hamsi Mansur; Susanti Sufyadi; Agus Hadi Utama (Bubungan Tinggi: Jurnal Pengabdian Masyarakat, 2024)
An analysis of the impact of the socialization and technical guidance program for Implementation of Independent Curriculum Independently was conducted to encourage the operationalization of educational units, particularly teachers, to access, learn, complete, and adapt teaching materials available on Platform Merdeka Mengajar (PMM) This involves using and utilizing the results of minimum competency assessments in class to design meaningful learning. The methods employed in this community service are socialization programs/in-service training and technical guidance/in-service training for Implementation of Independent Curriculum Independently. In-service training is an activity aimed at increasing the quality of educational personnel in performing their duties as professional teachers, particularly in utilizing Information and Communication Technology (ICT) for learning, such as adapting PMM to use and utilize the results of minimum competency assessments in class to design meaningful learning. The findings of this community service program include a participant satisfaction survey, where forums for teachers such as teacher working groups have successfully emphasized teaching focused on students' learning achievements (teaching at the right level). Teachers have been able to conduct formative assessments at the beginning of the learning process to assess students' learning achievements. In conclusion, Implementation of Independent Curriculum Independently is reflected in formulating learning outcomes, becoming learning objectives, and ways to achieve these learning objectives. This is demonstrated during the community service workshop, where teachers have successfully adapted to PMM by using and utilizing the results of minimum competency assessments  in class to design meaningful learning.